Paper-Derived Ferroelectric Ceramics: A Feasibility Study; Advanced Engineering Materials; Vol. 20, iss. 7 - Menge G. Georg; Lorenz H. Hannes; Fu Z. Zongwen; Eichhorn F. Franziska; Schader F. H. Florian; Webber K. G. Kyle; Fey T. Tobias; Greil P. Peter; Travitsky (Travitzky) N. Nakhum (2018, 2018)
Title screen